Power System Distributed Real-Time Simulations via Serverless Inspired Computing - Barbato, Giovanni S.; De Santis, Michele; Langella, Roberto; Picone, Antonio; Rubino, Luigi (International Conference on Environment and Electrical Engineering (Online), 2025)
Real-time simulations (RTSs) are popular in research because they can mimic real power-grid conditions. They are more flexible and scalable than physical laboratory tests are. To make RTSs more scalable, computing power is improved in different locations using shared networks resulting in distributed real-time simulation (DRTS). However, performing DRTS experiments is difficult and time-consuming, because it is necessary to coordinate different research setups to work together. Although serverless technology has improved, its use in DRTS is still time-consuming, particularly with many partners. This paper introduces a new DRTS method based on the server-less capabilities of the VILLAS framework for power systems using container blocks. Three experiments were performed using a simple linear time-varying circuit under sinusoidal conditions. In the first experiment, the simulations used DPSIM and EMT solvers of the open-source DPsim software with different time steps on one computer. In the second experiment, the proposed DRTS method is run on a single computer but using the proposed DRTS. In the third experiment, the simulation was run on two computers (emulating two labs) connected through a LAN. Experiment results show that container-based simulations are accurate in the presence of time-varying conditions in electrical networks and add flexibility to experimental design without the introduction of overhead in execution.